Mental health status of nurses during the covid-19 pandemic - Yovina Nuriati; Feriana Ira Handian; Afrihal Afif Ibadilah (PROFESSIONAL HEALTH JOURNAL, 2023)
Coronavirus Disease 2019 (COVID-19) is a new disease caused by the SARS Cov 2 virus, defined by WHO as an epidemic or pandemic. This causes the high number of confirmed cases of COVID-19, which can cause mental health problems. Mental health status that can be caused by nurses are depression, anxiety, stress, insomnia, somatic symptoms, PTSD, ASD, and suicidal ideation. The type of research used is literature review, with the results showing that from 12 journals a description of the status that affects mental health in nurses during the Covid-19 pandemic, namely mental health status depression (28.6%), anxiety (25.7%), stress (20%), insomnia ( 8.5%), somatic symptoms (5.7%), PTSD (5.7), ASD (2.9%), and having suicidal ideation (2.9%). Therefore, it is recommended that nurses be able to handle the factors that trigger the emergence of mental health disorders, one of which is by adapting to increasing COVID-19 care, hospital policies and support are also very necessary to minimize the occurrence of mental health disorders experienced by nurses during the COVID-19 pandemic. this. Keywords : mental health, nurses, and COVID-19